Magical Medicine On Television: Benin City, Nigeria - Lyons, Andrew P. (Journal of ritual studies, 1987)
This paper is an account of a Nigerian fundamentalist sect with strong American connections; the sect makes extensive use of television as a medium in order to propagate its message. In order to explain the rise of Bishop Idahosa's church which practices faith healing, the authors utilize Max Weber's notion of enchantment and emphasize the particular political and economic circumstances in southern Nigeria which are conducive to the development of such movements. Gramsci's concept of hegemony is utilized in order to explain the appeal of the TV preachers' message, and the effect of television on the message, audience and ritual is duly considered.